2014
DOI: 10.9738/intsurg-d-14-00030.1
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Surgery in the Elderly: A Comparative Experience of 400 Patients From an Italian University Hospital

Abstract: The aim of this study was to compare disease features and surgical complications of patients undergoing surgery under or over 65 years of age. We performed a retrospective review of patients undergoing thyroidectomy or lobectomy from January 1990 through January 2012 in our Institution. Patients aged over 65 years of age were compared with younger patients on a 1:1 ratio. A total of 2012 patients were operated on during the study period. Two-hundred patients aged . 65 years were compared with 200 patients , 65… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…While many studies show a similar increase in the incidence of RLN injury in older populations, the findings are not always uniform. For instance, Canonico et al 17 and Schwartz et al 18 reported nonstatistically significant increased rates of permanent and temporary RLN paralysis among patients aged 65 and 75 years, respectively. However, Sosa et al 1 found statistically significant increases in surgery-specific complications, including RLN injury and hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…While many studies show a similar increase in the incidence of RLN injury in older populations, the findings are not always uniform. For instance, Canonico et al 17 and Schwartz et al 18 reported nonstatistically significant increased rates of permanent and temporary RLN paralysis among patients aged 65 and 75 years, respectively. However, Sosa et al 1 found statistically significant increases in surgery-specific complications, including RLN injury and hypoparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Diaconescu et al [12] also reported that despite some additional risks related to comorbidities in patients over 65 years, patients may benefit of all types of conservative or radical thyroidectomies. Canonico et al [13] also reported that age did not increase the incidence of worse outcomes in patients who underwent thyroid surgery. On the other hand, in a population-based study on patients who underwent surgery for thyroid neoplasms, the rate of general postoperative complications was 6.5% and the rate of thyroid surgery-specific complications was 12.3%.…”
Section: Discussionmentioning
confidence: 93%
“…In our practice, we currently consider and propose prophylactic placement of NPWT to patients with at least two accepted predictors of SSI [3,17,21,28,29], or when there is a break in perioperative prophylactic measures [21]. Patients receiving steroids, frail (in the elderly with comorbidities-who are not excluded from major procedures in current practice [7,[93][94][95] ) or immunodepressed patients, and young patients suffering from IBD [7][8][9] are the ideal candidates to preventive NPWT after Colorectal surgery. It can be predicted that the use of preventive NPWT is cost-effective and well accepted in these patients.…”
Section: Clinical Trials On Preventive Npwt In Colorectal Surgerymentioning
confidence: 99%